Comparative 16SrDNA Gene-Based Microbiota Profiles of the Pacific Oyster (Crassostrea gigas) and the Mediterranean Mussel (Mytilus galloprovincialis) from a Shellfish Farm (Ligurian Sea, Italy) - VEZZULLI, LUIGI; STAGNARO, LAURA; GRANDE, CHIARA; TASSISTRO, GIOVANNI; CANESI, LAURA; PRUZZO, CARLA (Microbial Ecology, 2018)
The pacific oyster Crassostrea gigas and the Mediterranean mussel Mytilus galloprovincialis are two widely farmed bivalve species which show contrasting behaviour in relation to microbial diseases, with C. gigas being more susceptible and M. galloprovincialis being generally resistant. In a recent study, we showed that different susceptibility to infection exhibited by these two bivalve species may depend on their different capability to kill invading pathogens (e.g., Vibrio spp.) through the action of haemolymph components. Specific microbial-host interactions may also impact bivalve microbiome structure and further influence susceptibility/resistance to microbial diseases. To further investigate this concept, a comparative study of haemolymph and digestive gland 16SrDNA gene-based bacterial microbiota profiles in C. gigas and M. galloprovincialis co-cultivated at the same aquaculture site was carried out using pyrosequencing. Bacterial communities associated with bivalve tissues (hemolymph and digestive gland) were significantly different from those of seawater, and were dominated by relatively few genera such as Vibrio and Pseudoalteromonas. In general, Vibrio accounted for a larger fraction of the microbiota in C. gigas (on average 1.7-fold in the haemolymph) compared to M. galloprovincialis, suggesting that C. gigas may provide better conditions for survival for these bacteria, including potential pathogenic species such as V. aestuarianus. Vibrios appeared to be important members of C. gigas and M. galloprovincialis microbiota and might play a contrasting role in health and disease of bivalve species. Accordingly, microbiome analyses performed on bivalve specimens subjected to commercial depuration highlighted the ineffectiveness of such practice in removing Vibrio species from bivalve tissues.